Mechanical and chemical properties of CoCrFeNiMo0.2 high entropy alloy coating fabricated on Ti6Al4V by laser cladding. (May 2022) - Deng, Chong; Wang, Chao; Chai, Linjiang; Wang, Tao; Luo, Jun
Abstract: CoCrFeNiMo0.2 high entropy alloy (HEA) coating was successfully synthesized on Ti6Al4V sheet by laser cladding. Microstructural characteristics of the HEA coating were investigated by the combined use of multiple characterization techniques. The results indicate that the coating consists of body-centered cubic (BCC) and σ phases with a typical uniform dendrite microstructure. The hardness of the coating is ∼900 HV0.1, about 2.3 times that of the substrate. The coated Ti6Al4V alloy presents better oxidation resistance than Ti6Al4V at 600 °C due to a compact oxide layer rich in Cr element. Compared to the Ti6Al4V substrate, a lower wear rate is noted for the coating, demonstrating greatly improved wear resistance, especially at 600 °C. The wear mechanisms of the coating are dominated by abrasive wear and oxidative wear. A more positive corrosion potential value and lower corrosion current density value are found for the coating, indicating a better corrosion resistance than the Ti6Al4V alloy. In-depth analyses suggest that the improved surface performance is associated with combined contributions from the solid-solution strengthening and grain refinement hardening, as well as the addition of Cr element. Highlights: CoCrFeNiMo0.2 HEA coating is successfully fabricated on TC4 using laser cladding. The hardness of the HEA coating is about 900 HV0.1, 2.3 times that of the substrate. The wear resistance of TC4 is enhanced by the coating especially at high temperature. The HEA coating possesses excellent oxidation resistance owing to the Cr element.